Management of Intraoperative Miosis during Pediatric Cataract Surgery using Healon 5 - Jhanji, Vishal (Medknow Publications, 2011)
PURPOSE: We describe a technique for achieving pupillary dilatation in order to manage and counteract intraoperative miosis during pediatric cataract surgery using viscoadaptive viscoelastic (sodium hyaluronate 2.3%). MATERIALS AND METHODS: The technique of viscomydriasis was used in six eyes with pediatric cataracts with intraoperative pupillary miosis. RESULTS: Pupillary dilatation was achieved and maintained in all eyes throughout cataract surgery. All the surgical steps including anterior and posterior capsulorrhexis and aspiration were performed successfully. CONCLUSIONS: Viscomydriasis is a simple and effective technique for the management of intraoperative pupillary miosis during cataract surgery in pediatric eyes.